Odpowiedzi

Najlepsza Odpowiedź!
2010-02-04T18:30:31+01:00
A) [(3x²-xy)*(-2y)]*3x=(-6x²y+2xy²)*3x=-18x³y+6x²y²
b) (3x²-xy)*(-2y*3x)=(3x²-xy)*(-6xy)=-18x³y+6x²y²
c) [(3x²-xy)+(-2y)]*3x=(3x²-xy-2y)*3x=9x³-3x²y-6xy
d) [(3x²-xy)*3x]+(-2y*3x)=(9x³-3x²y)+(-6xy)=9x²-3x²y-6xy
1 5 1
2010-02-04T18:37:20+01:00
A: 3x²-xy B: -2y C: 3x


a) (A*B)*C
[(3x²-xy)*(-2y)]*3x
(-6x²y+2xy²)*3x
-18x³y+6x²y²

b) A*(B*C)
(3x²-xy)*(-2y*3x)
(3x²-xy)*(-6xy)
-18x³y+6x²y²

c) (A+B)*C
[(3x²-xy)+(-2y)]*3x
(3x²-xy-2y)*3x
9x³-3x²y-6xy

d) A*C+B*C
[(3x²-xy)*3x]+(-2y*3x)
(9x³-3x²y)+(-6xy)
9x²-3x²y-6xy